KLASIFIKASI KEKERINGAN TANAH MENGGUNAKAN METODE RIDGE REGRESSION - Setiawan, Febri; Hendryli, Janson (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Classifications drought land in a ridge regression aims to do classifications drought land in Jakarta and Bogor to satellite images landsat7 band 1, 2, 3, 4, 5 and 7, then selected area that have value NDSI (Normalized Difference Soil Index) more of or similar to 0.3. After that perform a division two categories, namely Y1 and Y2 with dummy dependent variable. A method of ridge regression used to shrink multicollinearity and the regression coefficient on the satellite images landsat7 band 1, 2, 3, 4, 5 and 7 by imposing penalty use constant bias. The results of classifications will shows broad drought land in Jakarta and Bogor. To testing the truth of the results of classifications drought the ground by ridge regression will be compared with their appearance in Google earth. Broad drought land highest in the Jakarta of 367.9740 km2 in May 2010 and in Bogor of 363.1266 km2 in June 2011 and the accuracy of the evaluation of classifications drought it can be said good because can reach value the accuracy of classifications drought land an average of 84.4688 % and standard deviations of 10.88442.